Entanglement in quantum dissipative Ising spin systems - Lozano, Gustavo Sergio (2007)
We study the behavior of entanglement estimators on chains of few quantum Ising spins coupled to an environment by means of Monte Carlo simulations. We analyze the ground state value of the von Neumann entropy and the concurrence of our spins system for different couplings with the quantum bath. © 2007 Elsevier B.V. All rights reserved.